A Review of Neuropathic Pain: From Diagnostic Tests to Mechanisms. Issue 1 (December 2017) - Truini, Andrea
Abstract Neuropathic pain develops when the somatosensory nervous system is affected by a lesion or disease. Diagnostic tests aimed at assessing somatosensory afferent pathway damage are therefore useful for diagnosing neuropathic pain. Neuropathic pain manifests with a range of different symptoms such as ongoing burning pain, squeezing or pressure pain, paroxysmal electric shock-like sensations, stabbing pain, or mechanical dynamic allodynia. The various types of neuropathic pain are associated with different underlying nerve fiber abnormalities. This article summarizes the available methods of somatosensory afferent pathway assessment and discusses the potential pathophysiology underlying the most representative neuropathic pain types, i.e., ongoing burning pain, paroxysmal pain, and mechanical dynamic allodynia. Funding: Pfizer, Italy.